Epitope tagging of yeast genes using a PCR-based strategy: more tags and improved practical routines - Knop, Michael; Pereira, Gislene; Zachariae, Wolfgang; Nasmyth, Kim; Schiebel, Elmar (Yeast, 1999)
Epitope tagging of proteins as a strategy for the analysis of function, interactions and the subcellular distribution of proteins has become widely used. In the yeast Saccharomyces cerevisiae, molecular biological techniques have been developed that use a simple PCR-based strategy to introduce epitope tags to chromosomal loci (Wach et al., 1994). To further employ the power of this strategy, a variety of novel tags was constructed. These tags were combined with different selectable marker genes, resulting in PCR amplificable modules. Only one set of primers is required for the amplification of any module. Furthermore, convenient laboratory techniques are described that facilitate the genetic manipulations of yeast strains, as well as the analysis of the epitope-tagged proteins. Copyright © 1999 John Wiley & Sons, Ltd.
Gesehen am 25.08.2017